Forecasting Bond Risk Premia Using Technical Analysis - GOH, Choo Yong, Jeremy (Institutional Knowledge at Singapore Management University, 2011)
While economic variables have been used extensively to forecast the U.S. bond risk premia, little attention has been paid to the use of technical indicators which are widely employed by practitioners. In this paper, we ﬁll this gap by studying the predictive ability of using a variety of technical indicators vis-a-vis the economic variables. We ﬁnd that the technical indicators have statistically and economically signiﬁcant in- and out-of-sample forecasting power. Moreover, we ﬁnd that utilizing information from both technical indicators and economic variables substantially increases the forecasting performances relative to using just economic variables.